A National Study of the Impact of Delayed Flap Timing for Treatment of Patients with Deep Sternal Wound Infection. Issue 2 (August 2017) - Sears, Erika D.; Momoh, Adeyiza O.; Chung, Kevin C.; Lu, Yu-Ting; Zhong, Lin; Waljee, Jennifer F.
Abstract : Background: This study aimed to evaluate the impact of delayed flap closure on mortality and resource use for treatment of deep sternal wound infection. Methods: The authors analyzed the Truven MarketScan Databases from 2009 to 2013 to identify adult patients who developed deep sternal wound infection after open cardiac surgery and who underwent flap closure for treatment. A multivariable logistic regression model was created to evaluate the relationship between mortality and flap timing. Multivariable Poisson regressions were used to investigate the relationship between flap timing and number of procedures, number of hospitalizations, and length of stay outcomes. A multivariable log-linear regression model was created for cost analysis. All analyses were adjusted for patient risk factors and treatment characteristics. Results: The authors identified 612 patients with deep sternal wound infection who underwent flap closure. The timing of flap closure was delayed more than 7 days after diagnosis in 39 percent of patients. Delayed time to flap closure greater than 3 days after diagnosis of infection was associated with higher mortality odds for delay 4 to 7 days (OR, 2.94) and delay greater than 7 days (OR, 2.75; p < 0.03), greater additional procedures for delay 4 to 7 days (incidence rate ratio, 1.72) and delay greater than 7 days (incidence rate ratio, 1.93; p < 0.001), and up to 43 percent longer hospital length of stay and 37 percent greater costs compared with patients undergoing flap closure 0 to 3 days after diagnosis. Conclusions: Delay in flap closure was associated with greater mortality and resource use. Prompt involvement of reconstructive surgeons may improve quality and efficiency of deep sternal wound infection care. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.Coding Perspective for this Article is on Page 399.